Analysis of Conflict of Interest Discourse on Online Fundraising Platforms Protect the Forest - Riski Rianda; Tri Guntur Narwaya; Nur Siva (Indonesian Journal of Business Analytics, 2024)
Ecology has become one of the main global issues today due to the worsening climate crisis around the world. LindungiHutan as the largest fundraising platform focusing on forest and environmental conservation in Indonesia can commercialise ecological issues through its digital means. This research aims to find out the conflict-of-interest discourse on LindungiHutan's online fundraising platform. The research was conducted qualitatively using the methods of text discourse analysis, social cognition, and social context. The results showed that LindungiHutan has commodified ecology through the nature campaign programme, collaboratree, corporatree, corporate social responsibility. LindungiHutan has collaborated with several companies that have contributed to the destruction of forests and the environment: MayBank, Mondelez International, DBS Bank, BCA Bank, PT Santos Jaya Abadi. LindungiHutan provides tree purchase packages divided into basic and additional services. LindungiHutan keeps the cost budget details and accountability report of each nature campaign confidential. The commodification of forests and the environment can also be seen from the establishment of a 5% administration fee policy for every fundraising campaign conducted by LindungiHutan.